2004
DOI: 10.1074/jbc.m400683200
|View full text |Cite
|
Sign up to set email alerts
|

Human Chorionic Gonadotropin Decreases Proliferation and Invasion of Breast Cancer MCF-7 Cells by Inhibiting NF-κB and AP-1 Activation

Abstract: The epidemiological data suggest that breast cancer risk decreases in women who complete full-term pregnancy at a young age. Studies on a rat breast cancer model indicate that human chorionic gonadotropin (hCG), a hormone that is present in very high levels during pregnancy, could be responsible for this decrease. These findings, as well as those demonstrating the presence of functional luteinizing hormone (LH)/ hCG receptors in human breast cells, prompted us to investigate the anti-proliferative and anti-inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 41 publications
7
31
0
Order By: Relevance
“…In agreement with these findings is the report indicating that the culturing of MCF7 cells with hCG results in a hCG/LH receptor-dependent decrease in cell proliferation and invasion across Matrigel membranes (25). This is interesting considering that it has been shown that women with hCG/LH receptor-positive tumors have longer metastasis-free survival (10).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…In agreement with these findings is the report indicating that the culturing of MCF7 cells with hCG results in a hCG/LH receptor-dependent decrease in cell proliferation and invasion across Matrigel membranes (25). This is interesting considering that it has been shown that women with hCG/LH receptor-positive tumors have longer metastasis-free survival (10).…”
Section: Resultssupporting
confidence: 78%
“…Other factors that could be found in commercial hCG in different proportions and have been shown to be toxic to Kaposi's sarcoma cells include lysozyme, low-molecularweight contaminants, and the eosinophil-derived neurotoxin RNase (31,34,35,38). Although previous studies have shown that hCG itself has a direct effect in breast cancer (13,25), additional experimentation is required to identify/purify hCG-associated factor and to determine its effects in breast cancer cells either alone or in conjunction with hCG. It is important to mention that, unlike breast cancer, Kaposi's sarcoma cells do not appear to express LH/hCG receptors (38).…”
Section: Resultsmentioning
confidence: 99%
“…It is not clear what is the exact basis for this discrepancy between these two models. However, there are many reports indicating the extra-gonadal actions of LH/hCG in other species including human (Carlson et al 2004, Eblen et al 2001, Lin et al 2003, Mishra et al 2003, Rao et al 2004a, Rao et al 2004b, Rao 2001a, Rao et al 2003, Toth et al 2001, Yang et al 2003a, Zygmunt et al 2002. Whether these species differences truly reflect the fundamental differences in sexual differentiation and female reproductive physiology or due to variations in the experimental settings remains to be established.…”
Section: Extra-gonadal Phenotypes In Lurko Micementioning
confidence: 99%
“…However, reports on the biological consequences of elevated LH and/or b-HCG levels and expression of their receptor in breast tissue are conXicting. On one hand, in vitro observations suggest an anti-proliferative eVect of b-HCG on breast cancer cell lines (Rao Ch et al 2004) which could explain the decreased incidence of malignant breast tumors in early pregnancy. On the other hand, animal studies demonstrate that the development of the rudimentary ductal network can be boosted by creating LHbCTP transgenic mice resulting in extensive epithelial hyperplasia and subsequent development of malignant tumors in case of chronic exposure to elevated LH levels (Mann et al 2003).…”
Section: Introductionmentioning
confidence: 98%